Pancreatic exocrine insufficiency and pancreatic enzyme replacement therapy in patients with advanced pancreatic cancer: A systematic review and meta-analysis - de la Iglesia, Daniel (United European Gastroenterol J, 2020)
BACKGROUND: Pancreatic cancer is the fourth leading cause of cancer mortality. Most patients are diagnosed with advanced pancreatic cancer, either at locally advanced or metastatic stages, and have a high rate of malnutrition and weight loss which are associated with poor outcomes. Pancreatic exocrine insufficiency is one of the causes of malnutrition and weight loss in these patients. The prevalence and clinical consequences of pancreatic exocrine insufficiency in advanced pancreatic cancer are poorly investigated with heterogeneous results. We sought to determine the prevalence and clinical consequences of pancreatic exocrine insufficiency and the effect of pancreatic enzyme replacement therapy in patients with advanced pancreatic cancer by systematic review and meta-analysis. METHODS: Scopus, Medline, and Embase were searched for cohort studies or randomised clinical trials reporting pancreatic exocrine insufficiency and/or the effect of pancreatic enzyme replacement therapy in patients with advanced pancreatic cancer. We considered pancreatic exocrine insufficiency as an abnormal result on direct and/or indirect pancreatic exocrine function tests. Pancreatic enzyme replacement therapy was evaluated by its effect on survival and quality of life in patients with advanced pancreatic cancer. RESULTS: A total of 11 studies were included; seven studies reported the prevalence of pancreatic exocrine insufficiency and seven the effect of pancreatic enzyme replacement therapy in advanced pancreatic cancer. The pooled prevalence of pancreatic exocrine insufficiency in advanced pancreatic cancer was 72% (95% confidence interval: 55–86%), being significantly higher when tumours were located in the pancreatic head (relative risk = 3.36, 1.07–10.54; p = 0.04) six studies investigated the impact of pancreatic enzyme replacement therapy on survival/quality of life. Pancreatic enzyme replacement therapy was associated with 3.8 months (95% confidence interval: 1.37–6.19) survival benefit. Patients receiving pancreatic enzyme replacement therapy had a trend towards a better quality of life. Conclusions The prevalence of pancreatic exocrine insufficiency in advanced pancreatic cancer is substantial and its treatment can improve the outcomes of these patients.